A review of the carbonaria-subgroup of Fannia Robineau-Desvoidy (Diptera: Fanniidae), with descriptions of two new species from China - Wang, Ming-Fu; Zhang, Dong; Zheng, Shuang; Zhang, Chun-Tian (Zootaxa, 2009)
The Fannia carbonaria-subgroup belongs to the Fannia carbonaria-group Chillcott, 1961. The world fauna of this subgroup is reviewed, the diagnostic features of the subgroup are redefined, and a key to the males of the known species is given. Two new species from China are described: F. dorsovittata Wang sp. nov. and F. subfuscitibia Wang sp. nov.. To facilitate comparisons of the species, Fannia corvina (Verrall), Fannia imperatoria Nishida and Fannia xiaoi Fan are redescribed. Geographic distributions of the species of the subgroup are updated. The systematic position and distribution patterns of the F. carbonaria-subgroup are discussed.